Nudopeza, a New Genus of Neotropical Micropezidae (Diptera, Micropezidae, Taeniapterinae) - Stephen A. Marshall (Taxonomy)
The Neotropical genus Nudopeza (Micropezidae, Taeniapterinae) is described for a group of 41 species, including Nudopeza tapanti sp. nov. (type species) and Nudopeza pronigra (Hennig) n. comb. for Grallipeza pronigra Hennig 1934, Nudopeza arcuata (Hennig) n. comb. for Grallipeza arcuata Hennig 1934, and the following 38 additional new species: N. cegex sp. nov, N. cura sp. nov, N. duplitheca sp. nov, N. gilli sp. nov., N. glypha sp. nov., N. gracei sp. nov., N. hansoni sp. nov., N. horologia sp. nov., N. laselva sp. nov., N. mephitis sp. nov., N. mexicana sp. nov., N. micromephitis sp. nov., N. nigrivertex sp. nov., N. nigriscutellum sp. nov., N. nudarcuata sp. nov., N. penai sp. nov., N. palenque sp. nov., N. paramephitis sp. nov., N. peruviensis sp. nov., N. quadrivitta sp. nov., N. ruficincta sp. nov., N. rutilans sp. nov, N. sirena sp. nov., N. sumaco sp. nov., N. trinidadensis sp. nov., N. uniseta sp. nov., N. variterga sp. nov., N. venezuelensis sp. nov., N. verpa sp. nov., N. versivitta sp. nov., N. viriola sp. nov., N. viva sp. nov., N. yungasensis sp. nov., N. zarza sp. nov., N. zostera sp. nov., N. zumera sp. nov., N. zygoma sp. nov., and N. zytha sp. nov.